If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -3a = 3(ax + 3a + 2x) Reorder the terms: 7 + -3a = 3(3a + ax + 2x) 7 + -3a = (3a * 3 + ax * 3 + 2x * 3) 7 + -3a = (9a + 3ax + 6x) Solving 7 + -3a = 9a + 3ax + 6x Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-9a' to each side of the equation. 7 + -3a + -9a = 9a + 3ax + -9a + 6x Combine like terms: -3a + -9a = -12a 7 + -12a = 9a + 3ax + -9a + 6x Reorder the terms: 7 + -12a = 9a + -9a + 3ax + 6x Combine like terms: 9a + -9a = 0 7 + -12a = 0 + 3ax + 6x 7 + -12a = 3ax + 6x Add '-3ax' to each side of the equation. 7 + -12a + -3ax = 3ax + -3ax + 6x Combine like terms: 3ax + -3ax = 0 7 + -12a + -3ax = 0 + 6x 7 + -12a + -3ax = 6x Add '-7' to each side of the equation. 7 + -12a + -7 + -3ax = -7 + 6x Reorder the terms: 7 + -7 + -12a + -3ax = -7 + 6x Combine like terms: 7 + -7 = 0 0 + -12a + -3ax = -7 + 6x -12a + -3ax = -7 + 6x Reorder the terms: 7 + -12a + -3ax + -6x = -7 + 6x + 7 + -6x Reorder the terms: 7 + -12a + -3ax + -6x = -7 + 7 + 6x + -6x Combine like terms: -7 + 7 = 0 7 + -12a + -3ax + -6x = 0 + 6x + -6x 7 + -12a + -3ax + -6x = 6x + -6x Combine like terms: 6x + -6x = 0 7 + -12a + -3ax + -6x = 0 The solution to this equation could not be determined.
| 0.5x+3=0.25x+12 | | 16x+3=2(112x+32) | | x^2-5xy-50y^2=0 | | x+(x*36)=191 | | 5.659-z=127+175.18-31.4 | | 7-3a=3(ax+3a-2x) | | 111.615-y=110+128.8-70.5 | | 2x/e^x | | 14.5+43+17.6= | | 7x+79=3x+103 | | 6x^3-x(7x+10)=0 | | 7c-21c^2=0 | | 0.5x+10=23 | | 8-2y-y=0 | | 20m^3-10m^2=0 | | 12k-24k^2=0 | | -7-7x+9x^2=-x | | 3x^2+3y^2+18x-12y+6m+3=0 | | -4/3-7/4y=-9/5 | | (x+80)+2(x+80)=X | | 140.3265-81.78= | | 0=-2x(3x-1)(4x+3) | | 81k-9k^2=0 | | 5x+12=-13x+17 | | 81.78-140.3265= | | 4=2(v-7)-8v | | T=72-82 | | -4+19=m-8 | | 100a^2-25a=0 | | log41/64= | | 5b^2-15b=0 | | y=0.75(140)+17 |